Investigation of the Sedimentation Property of Backfill Material on the Basis of Rheological Test: A Case Study of Iron Tailings - Yong Wang; Aixiang Wu; Lianfu Zhang; Hongjiang Wang; Fei Jin (Journal of Chemistry)
Sedimentation of filling materials could cause pipe blocking accident in mines. However, few quantitative characterization studies have investigated the sedimentation characteristics of filling materials. In this study, the sedimentation property of iron tailings with a cement-sand ratio of 1 : 4 and mass concentration of 73%∼82% was investigated based on rheology measurements. Results showed that shear stress increased as shear rate rose from 0 s−1 to 120 s−1. The shear stress increased as the filling material concentration increased as well. However, when the shear rate was reversed from 120 s−1 to 0 s−1, the shear stress presented an increase-constant-decrease change pattern as the mass concentration increases in the rheological curve. Accordingly, the sedimentation performance of iron tailings filling material was divided into three types: intense sedimentation (the ascending rheological curve) in the mass concentration range of 73%∼76%, slight sedimentation (the constant rheological curve) in the mass concentration range of 77%∼79%, and almost no sedimentation (the descending rheological curve) in the mass concentration range of 80%∼82%. The associated mechanism involving slurry mass concentration-rheological curves-sedimentation performance was illustrated. A correlation between the pipeline rheology and filling material sedimentation performance was established, which provides a practical guide to avoid pipeline blocking while transporting the filling material.